2011
DOI: 10.1186/1471-2377-11-115
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features of headache associated with mobile phone use: a cross-sectional study in university students

Abstract: BackgroundHeadache has been reported to be associated with mobile phone (MP) use in some individuals. The causal relationship between headache associated with MP use (HAMP) and MP use is currently undetermined. Identifying the clinical features of HAMP may help in clarifying the pathophysiology of HAMP and in managing symptoms of individuals with HAMP. The aim of the present study is to describe the clinical features of HAMP.MethodsA 14-item questionnaire investigating MP use and headache was administered to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 34 publications
5
36
0
2
Order By: Relevance
“…The studies of headache occurrence on prolonged cell/mobile phone calls (typically well over one hour) listed under Chu et al, 2011 in Table 3 also suggest the assumed doseresponse relationship (see also Chia et al, 2000;Oftedal et al 2000 andearlier citations listed in Frey, 1998). Because such headaches only occur with prolonged cell/mobile M a n u s c r i p t phone calls, these studies also provide evidence for a dose-response relationship because low doses are ineffective.…”
Section: Consistency Within the Different Epidemiological Studies Andmentioning
confidence: 95%
See 1 more Smart Citation
“…The studies of headache occurrence on prolonged cell/mobile phone calls (typically well over one hour) listed under Chu et al, 2011 in Table 3 also suggest the assumed doseresponse relationship (see also Chia et al, 2000;Oftedal et al 2000 andearlier citations listed in Frey, 1998). Because such headaches only occur with prolonged cell/mobile M a n u s c r i p t phone calls, these studies also provide evidence for a dose-response relationship because low doses are ineffective.…”
Section: Consistency Within the Different Epidemiological Studies Andmentioning
confidence: 95%
“…There is also a strong association where important new exposures occur -this is clearly the case with all of the studies of people living near cell/mobile phone base stations, listed in Table 3 and also with the two studies of people who become exposed to radiation from smart meters. The studies listed in Table 3 under Chu et al, 2011 (see also Chia et al, 2000;Oftedal et al 2000) are of a special type. Here people making very long (over 1 h.) cell/mobile phone calls develop headaches an hour or more following the initiation of the long call.…”
Section: Criteria For Assessing Causality In Epidemiological Studiesmentioning
confidence: 99%
“…It is reported that during prolonged use of mobile phones, individuals feel a burning sensation in their auricles which might be associated with warming of the device. 9 Also in a study by Kapdi et al the health hazards of electromagnetic radiation exposure in terms of thermal effects from mobile phones was emphasized. 10 During playing games, watching videos or texting the phone is held in the left palm facing up the screen and allowed for the right-hand swiping.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have suggested radiofrequency (RF) emitted from mobile phones as one of the possible causes of these symptoms, however, recent studies have documented no association between these two factors [23]. It has been suggested that the effect of heat or noise from mobile phone use [24] or the nocebo effect may be the possible cause [23,[25][26][27] for these health symptoms. Nonetheless, with the lack of studies regarding the effect of accumulated exposure to radiofrequency in children, and no solid conclusion over the question of whether children are more susceptible to the exposure of radiofrequency waves [28,29], it is still advised that children take precautionary measures to avoid unnecessary exposure to mobile phones [19].…”
Section: Page 6 Ofmentioning
confidence: 99%